Reliability optimization methods: A systematic literature review - Singla Shakuntla; Mangla Diksha; Kumar Malik Ajender; Muhammad Modibbo Umar (Yugoslav Journal of Operations Research)
The industry is a system that combines parallel, series, or combination of two to transform cheap raw materials into valuable goods. Occasionally, the system may also consist of subunits that can be arranged in various ways. The series arrangement is represented when the system fails completely because of the failure of every subunit (also called complete failure); conversely, when the system operates with low efficiency, i.e., this illustrates the arrangement in a parallel fashion in a reduced state (called partial failure). In order to learn about the advancements in the field of reliability theory and to determine which research methods are most frequently employed by researchers, a brief survey covering the years 1958 to 2024 was conducted for the paper. The overall impact of the functioning system's state on its dependability is further discussed in this study by reviewing 112 papers selected from the study of 220 papers taken from reputed journals. In this study, we've taken into account the reviews of numerous researchers and investigated the most popular approach for overcoming others' obstacles. Additionally, which variables influence the primary reliability metrics in their work and how? These are complemented by graphics and table.